Liquidity, redistribution, and the welfare cost of inflation - Jonathan Chiu; Miguel Molico (Bank of Canada, 2007)
This paper studies the long run welfare costs of inflation in a micro-founded model with trading frictions and costly liquidity management. Agents face uninsurable idiosyncratic uncertainty regarding trading opportunities in a decentralized goods market and must pay a fixed cost to rebalance their liquidity holdings in a centralized liquidity market. By endogenizing the participation decision in the liquidity market, this model endogenizes the responses of velocity, output, the degree of market segmentation, as well as the distribution of money. We find that, compared to the traditional estimates based on a representative agent model, the welfare costs of inflation are significantly smaller due to distributional effects of inflation. The welfare cost of increasing inflation from 0% to 10% is 0.62% of income for the U.S. economy and 0.20% of income for the Canadian economy. Furthermore, the welfare cost is generally non-linear in the rate of inflation, depending on the endogenous responses of the liquidity market participation to inflation and liquidity management costs.
Keywords: E40; E50; 330; Inflation: costs and benefits; Inflation; Außenhandelsbeschränkung; Betriebliche Liquidität; Verteilungswirkung; Wohlfahrtseffekt; Kanada; USA